How the COVID-19 pandemic has affected rheumatology research - Moreyra, Paula Alba; Berenbaum, Francis; Danda, Debashish; Grötsch, Bettina; Stones, Simon R.; Viswanathan, Sowmya (Nature Reviews Rheumatology, 2022)
The COVID-19 pandemic has put pressure on researchers around the world. In this Viewpoint, six rheumatology researchers at different career stages and from different regions discuss the difficulty of conducting research during the pandemic, and also reflect on how the pandemic has changed their attitudes towards research and their plans for the future.
CRIS-Team WoS Importer:2022-01-21

Inflammatory activation of the FcγR and IFNγR pathways co-influences the differentiation and activity of osteoclasts - Grötsch, Bettina; Schachtschabel, Elisabeth; Tripal, Philipp; Schmid, Benjamin; Smith, Ana-Suncana; Schett, Georg; Bozec, Aline (Frontiers in Immunology, 2022)
Osteoclasts are polykaryons formed by cell–cell fusion of highly motile progenitors of the myeloid lineage. Osteoclast activity can preserve skeletal strength and bone homeostasis. However, osteoclasts are responsible for bone destruction in rheumatoid arthritis (RA). Fc receptors activated by IgG immune complexes (IC) can boost osteoclast differentiation and bone loss in the course of RA. In contrast, interferon (IFN) γ secreted by immune cells blocks osteoclast activation. Despite their hypothetical importance in the regulation of osteoclast differentiation in RA, the interconnection between the two pathways has not been described so far. Here, we show by total internal reflection fluorescence (TIRF) microscopy that FcγR3 and IFNγ receptor (IFNγR) locate at close vicinity to each other on the human osteoclast surface. Moreover, the average distance increases during the differentiation process. Interestingly, FcγR and IFNγR activation shapes the position of both receptors to each other. Surprisingly, the inhibitory action of IFNγ on in-vitro human osteoclast differentiation depends on the osteoclast differentiation stage. Indeed, IFNγR activation in early osteoclast precursors completely inhibits the formation of polynucleated osteoclasts, while in premature osteoclasts, it further enhanced their fusion. In addition, gene expression analyses showed that IFNγR activation on early precursor cells but not on premature osteoclasts could induce FcγR expression, suggesting a co-regulation of both receptors on human osteoclast precursors. Phosphokinase array data of precursor cells demonstrate that the observed divergence of IFNγR signaling is dependent on the mitogen−activated protein kinase (MAPK) downstream signaling pathway. Overall, our data indicate that FcγR and IFNγR signaling pathways co-influence the differentiation and activity of osteoclasts dependent on the differentiation state, which might reflect the different stages in RA.
CRIS-Team Scopus Importer:2022-10-07
Keywords: FcγR3; IFNγR; IFNγR signaling; ITAM signaling; Osteoclast; rheumatoid arthritis (RA)

Osteocyte necrosis triggers osteoclast-mediated bone loss through macrophage-inducible C-type lectin - Andreev, Darja; Liu, Mengdan; Weidner, Daniela; Kachler, Katerina; Faas, Maria; Grüneboom, Anika; Schlötzer-Schrehardt, Ursula; Munoz, Luis Enrique; Steffen, Ulrike; Grötsch, Bettina; Killy, Barbara; Krönke, Gerhard; et al. (Journal of Clinical Investigation, 2020)
Although the control of bone-resorbing osteoclasts through osteocyte-derived RANKL is well defined, little is known about the regulation of osteoclasts by osteocyte death. Indeed, several skeletal diseases, such as bone fracture, osteonecrosis, and inflammation are characterized by excessive osteocyte death. Herein we show that osteoclasts sense damageassociated molecular patterns (DAMPs) released by necrotic osteocytes via macrophage-inducible C-type lectin (Mincle), which induced their differentiation and triggered bone loss. Osteoclasts showed robust Mincle expression upon exposure to necrotic osteocytes in vitro and in vivo. RNA sequencing and metabolic analyses demonstrated that Mincle activation triggers osteoclastogenesis via ITAM-based calcium signaling pathways, skewing osteoclast metabolism toward oxidative phosphorylation. Deletion of Mincle in vivo effectively blocked the activation of osteoclasts after induction of osteocyte death, improved fracture repair, and attenuated inflammation-mediated bone loss. Furthermore, in patients with osteonecrosis, Mincle was highly expressed at skeletal sites of osteocyte death and correlated with strong osteoclastic activity. Taken together, these data point to what we believe is a novel DAMP-mediated process that allows osteoclast activation and bone loss in the context of osteocyte death.
CRIS-Team Scopus Importer:2020-10-16